Adolescent girls' experiences of basketball in Australian and Japanese clubs. Issue 2 (4th May 2017) - Light, Richard; Yasaki, Wataru
ABSTRACT: Despite recognition of the influence of social and cultural contexts on young people's participation in youth sport, there are a limited number of studies that have identified how culture shapes the nature of participation and how it influences experience. This article reports on a study that inquired into what adolescent girls (13–16 years) enjoy about playing basketball in Japan and Australia and in which the cultural context emerged as a significant influence upon experience and enjoyment. Adopting grounded theory methodology, data were generated through an initial questionnaire and three subsequent rounds of semi-structured interviews with six girls in the team at clubs in Melbourne, Australia, and Tokyo, Japan.